Assessment of stakeholder engagement practices of it projects: A case study of GCB Bank Limited Ghana - Odum, Aba Esuon (2021)
A thesis submitted to the Department Of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi in partial fulfilment of the requirement for theAward Degree of